Diet Quality: A Neglected Parameter in Children With Food Allergies. A Cross–Sectional Study - Kalmpourtzidou, Aliki; Xinias, Ioannis; Agakidis, Charalampos; Mavroudi, Antigoni; Mouselimis, Dimitrios; Tsarouchas, Anastasios; Agakidou, Eleni; Karagiozoglou-Lampoudi, Thomai (Frontiers in Pediatrics, 2021)
Background-Objective: With recent evidence suggesting that growth is no longer considered a major issue in children with food allergies (FA) on elimination diet, priority has shifted to diet quality to establish healthy eating patterns and prevent non-communicable diseases. The Diet Quality Index – International (DQI-I) could be useful for assessing the overall diet quality of FA-children. This study aimed to evaluate the impact of elimination diet on DQI-I in children with FA and the accuracy of DQI-I in reflecting nutrient intake. Materials-methods: In a prospective, cross-sectional, cohort study of FA-children (2-14 years), nutritional intake was evaluated using a 7-day food frequency questionnaire, 24-hour dietary recall, and the DQI-I. Results: Of the 76 children recruited, 44.7% had multiple allergies. Mean overall DQI-I score was 52 points, with only 28% of participants having good overall DQI-I (≥60 points). DQI-I moderation and balance were the most affected domains. Participants with multiple allergies had higher DQI-I moderation and balance and lower vitamin D and Ca intake. Compared to toddlers, schoolchildren had higher DQI-I variety and lower moderation and received higher vitamin B2, vitamin B12, Ca, P, and Zn. The number of allergies, age, and milk avoidance were independently associated with adjusted DQI-I moderation and balance, energy, and certain micronutrient intake. Higher percentages of participants with good DQI-I received adequate amounts of Mn and vitamins A, B6, C, and folate than those with poor DQI-I. Conclusions: In children with FA on elimination diet, DQI-I accurately captured the deflection of diet quality related to the development of chronic, non-communicable diseases through its moderation and balance components. This is DQI-I’s main purpose as a healthy diet indicator and would be a useful tool responding to the needs of the contemporary shifting of priorities in FA-children’s diet from quantity to quality. Nevertheless, it does not accurately reflect the intake of certain micronutrients potentially compromised by elimination diets. Therefore, regular nutritional assessment utilizing both the DQI-I and tools assessing individual nutrient intakes along with professional nutrition counseling should be integral parts of the individualized management of children with FA to ensure adequate nutrient intake and establish healthy dietary patterns.